The caring hand that cripples: The East German labor market after reunification (detailed version) - Dennis J. Snower; Christian Merkl (Kiel Institute for the World Economy (IfW), 2006)
The East German labor market has hardly made any progress since German reunification, despite massive migration flows and support from the West. We argue that East Germany is in trouble precisely because of the support it has received. This paper explores the phenomenon of "the caring hand that cripples," arising from bargaining by proxy, the adoption of the West German welfare system and the associated employment persistence. Even the steady decrease of labor cost (normalized by productivity) since the beginning of the nineties did not help to kick start the East. We suggest that labor force participants fell into "traps," concerning low skills, ageing of the workforce, labor-saving capital and skills, capital underutilization, and unemployment arising from the decline of the tradeable sector.
Keywords: J3; E24; 330; German unification; Labor markets; Labor market traps; Arbeitslosigkeit; Arbeitsmarktflexibilisierung; Sozialstaat; Wirtschaftliche Anpassung; Subvention; Neue Bundesländer